STRATEGI PEMASARAN PT. ALLIANCE VAST TOURS TERHADAP WISATAWAN PENGGUNA JASA PERJALANAN - Pradipa Artawan, I Putu; Kusuma Negara, I Made; Leli Kusuma Dewi, Luh Gede (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 2 (2014): Jurnal IPTA (December 2014)DO - 10.24843/IPTA.2014.v02.i02.p04)
Indonesia especially Bali has a huge potential in the field of tourism. It can be seen from a wide range of beautiful natural scenery, culture, history of the nation, festivals and ceremonies are unique, different kinds of art and crafts, and a number of very attractive place for tourists throughout the year . The study aims is to determine the marketing strategy of the company's tour packages PT. Vast Alliance Tour who can be success to attract tourists to use the services at PT. Vast Alliance Tour. The analysis using SWOT to determine what the is right strategy which can be used to market package of PT. Vast Alliance Tour. This study led to the conclusion that that the marketing strategies undertaken by PT. Vast Alliance Tour in promoting its products through website, brochures, and sales calls. Products offered by PT. Vast Alliance Tour package in the form of packages like rafting, water sports, cruise, spa, and and much more. Strategy undertaken in this study using the SWOT analysis is to combine the strengths and opportunities that can cover the weaknesses and threats that exist in the relevant product market.
Keywords: Marketing of Tourism, Travel Industry